Correlates of perceived HIV-related stigma among HIV-positive pregnant women in rural Mpumalanga province, South Africa. Issue 2 (4th March 2019) - Ramlagan, Shandir; Sifunda, Sibusiso; Peltzer, Karl; Jean, Jenny; Ruiter, Robert A.C.
Abstract : The study investigated correlates of perceived HIV-related stigma among 673 HIV-positive women from rural Mpumalanga province, South Africa (mean age 28 years old, SD = 5.73 years). The women completed measures of HIV-related stigma experience and related personal factors. Following multivariable logistic regression, results showed that lack of male involvement during the ante-natal visits was significantly associated with all four perceived HIV-related stigma factors. Lower income, intimate partner violence (IPV), lower education, and experienced HIV-related stigma were associated with a combination of the four components of perceived HIV-related stigma. From these findings, we conclude that higher levels of education, income, and partner involvement are protective factors against perceived HIV-related stigma, at multiple layers. Improving on adult education and income generating activities can help in reducing HIV-related stigma. Male partner involvement in their partner's pregnancy, the initiation of support groups for both women and men, as well as community-based IPV prevention interventions may help to reduce perceived HIV-related stigma among women living with HIV.